IIHR, Bengaluru heralding golden revolution - Dinesh, M R; Sankaran, M (Indian Horticulture, 2019)
The Indian Institute of Horticultural Research (IIHR), Bengaluru, was established by the Indian Council of Agricultural Research on 5 September 1967 at the ICAR Headquarters, New Delhi. Subsequently, the institute was shifted to Bengaluru, Karnataka, at Hessaraghatta on 1 February 1968. Dr GS Randhawa was the Founder Director. The institute conducts basic, strategic, anticipatory and applied research on various aspects of horticultural crops, viz. fruits, vegetables, ornamentals and medicinal plants in order to improve their productivity, quality and utility. The institute took over the erstwhile National Hortorium of Karnataka Government at Hessaraghatta spread over 24.7 ha and started its activities. Later on, the institute acquired an additional 238 ha of land from the surrounding villages. The institute spread its sphere of research activities to the length and breadth of the nation by establishing its experimental stations at Lucknow, Nagpur, Ranchi, Godhra, Chettalli and Gonikoppal. Over the years, the experiment stations at Lucknow, Nagpur, Ranchi, and Godhra have grown in size and today they stand as independent institutes. As of now, the IIHR has its main research station at Hessaraghatta, Bengaluru, and Horticultural Experiment Stations at Bhubaneswar in Odisha and Chettalli in Karnataka, with two Krishi Vigyan Kendras located at Gonikoppal in Kodagu and Hirehalli in Tumkur districts of Karnataka. Apart from this, the institute houses Project Coordinating Unit of All India Co-ordinated Research Project on Tropical Fruits at its main campus. The IIHR has given birth to 2 National institutes, 3 NRCs (banana, pomegranate and grapes) and 1 Directorate (medicinal plants), as on today, says Dr MR Dinesh, Director, IIHR, Bengaluru.